АНАЛІТИЧНА ОЦІНКА ДЕЯКИХ ПАРАМЕТРІВ РЕГІОНАЛЬНОЇ ЕКОНОМІЧНОЇ СИСТЕМИ - Vasylenko, D.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2011)
The paper reviews some parameters of the regional economic system. The changes which took place in the period from 2001 till 2009 were determined. It was set that in the regional economic system the relations connected with a continuing transformation process in the social production prevailed. The conclusions are made that now the region’s economy experiences a difficult period, and the way out is finding «the points of growth» which will allow to develop all the elements of the regional economic system.